Reasons for patients leaving against medical advice in emergency department at a tertiary hospital, Nepal - Sharma G, Ram Prasad; Adhikari, Sushila Kumari; Rajbanshi, Laxmi (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Leaving Against Medical Advice (LAMA) presents significant challenges in planning and delivering healthcare services. It often leads to worsened patient outcomes and increased rates of readmission. This study aimed to identify the reasons behind patients leaving against medical advice in the emergency department of a tertiary hospital. Methods: A descriptive cross-sectional study was conducted at a tertiary hospital in central Nepal from February 1, 2024 to July 31, 2024. Patients who requested to leave the healthcare setting without complete treatment and arrange further care or treatment elsewhere were included; 214 participants were included in this study. Data were collected using a self-structured questionnaire developed based on a review of previous studies and analyzed using SPSS version 20 for descriptive statistics. Results: Among the 214 participated in this study. LAMA cases were predominantly observed among men (62.1%), married individuals (83.6%), those who were employed (68.7%), and those who were self-paying (97.7%). Two important reasons for LAMA were financial constraints (30.8%) and the perception of improved health (26.2%). Other reasons included personal issues such as caregiving and work commitments (10.7%), lack of health insurance (8.4%), preference for outpatient treatment (6.1%), dissatisfaction with high hospital charges (3.3%), delays in specialist consultations (1.9%), and poor communication about the treatment plan (0.5%). Conclusions: Financial difficulty was identified as the primary reason for LAMA followed by the perception of feeling better. These findings can help healthcare providers plan targeted interventions and implement measures to reduce LAMA rates and improve patient outcomes.